Modern American Literature - Cerrito, Joann, editor 652101; DiMauro, Laurie, editor 391311; Gale Group (Online service) 651863 (Farmington Hills : St. James Press (an imprint of Gale), 1999)
Provides insight into the careers of nearly 500 20th-century American writers, including black and women writers. Entries include important critical excerpts, chronologically arranged and collected from a wide variety of sources such as books, scholarly journals, general periodicals and newspapers.